Purification and partial characterization of serum immunoglobulins of - Sood, Neeraj; Raja Swaminathan, T; Rathore, Gaurav (Indian Journal of Fisheries, 2011)
Channa striatusimmunoglobulin (Ig) was purified from serum by affinity chromatography using bovine serum albumin ascapture ligand. The purified Ig had a molecular weight (MW) of 820 kDa as determined with gel filtration chromatography.Under reducing SDS-PAGE, the Ig molecule was shown to consist of two subunits, heavy and light chain having a MW of70.4 and 25.3 kDa, respectively. A high MW band was observed in non-reducing SDS-PAGE, suggesting tetrameric structure.